PENGARUH TINDAKAN PENAGIHAN AKTIF TERHADAP PENCAIRAN TUNGGAKAN PAJAK (Studi pada Kantor Pelayanan Pajak Pratama Ambon Tahun 2012-2016)” - Revy Wilhelmina Silooy (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
This study aims to examine the effect of active billing (Rebuke, Forced Letter and Sita) actions partially and simultaneously on the disbursement of tax arrears. The population in this study are taxpayers who have businesses registered in the Ambon Primary KPP area. The sample in this study are corporate taxpayers and private business people who have a NPWP. Samples were taken using purposive sampling technique. Data collection methods carried out are interview and documentation methods. Analysis of the data used in this study through data obtained in the field and library data. The results showed that the active collection action in the form of Reprimand and Forced Letter partially did not have a significant effect on the disbursement of tax arrears, while the Order to Conduct Foreclosure partially had a significant effect on the disbursement of tax arrears. This means that efforts are still needed to increase the awareness of taxpayers in fulfilling their obligations. Keywords: Active collection action, Reprimand, Sita Letter, Letter of Execution of Tax Confiscation, tax arrears, awareness of paying taxes, knowledge and understanding of tax regulations, good perception of the effectiveness of the tax system.